The Coronavirus Pandemic and Business: A Time of Collapse or a Time of New Opportunities? - Petrovich, Garnov Andrey; Alekseevna, Prodanova Natalia; Yuryevna, Garnova Victoria; Yurievna, Kamchatova Ekaterina; Ivanovna, Zatsarinnaya Elena; Sergeevna, Latushkina Tatyana (International Journal of Psychosocial Rehabilitation, 2020)
The era of scientific and technological revolution that began in the second half of the twentieth century brought a powerful rise of technocratic and scientific ideas, which culminated in the development of concepts of industrial society, post-industrial society and information society. These concepts have found their concretization in the theories of consumer society, leisure society, technotronic, technocratic and computerized society. The article critically analyzes the concept of technological determinism, which is still put forward as a panacea for the treatment of all social diseases. It is shown that scientific and technological progress creates objective grounds for social progress, but is not able to solve any of the global problems of our time. From the author’s point of view, these problems themselves are determined not so much by the development of science and technology as by the form of ownership of the means of production. The article also reveals the main reason for the global crisis in 2020: the virus-economic crisis continues to gain momentum both in the world and in Russia. (back in March 2020, many experts expressed the hope that the world economy could avoid a recession (i.e., a fall).)